PENGUJIAN TEORI FRAUDPENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAANPERTAMBANGANDIINDONESIA - I Made Laut Mertha Jaya; Ajeng Ayu Ambarwati Poerwono (Akuntabilitas, 2019)
This study wasto determine the effect of financial targets, financial stability, external pressure, ineffective monitoring, the nature of industry, change in auditors, rationalization, change of directors, and CEO's picture of fraudulent financial statements in mining companies in Indonesia. This study uses descriptive quantitative methods. Technique of collecting data through documentation. The data used in this study are secondary data in the form of annual reports or annual reports of mining sector companies listed on the Indonesia Stock Exchange for the period 2013-2017. Next, the data was tested using multiple linear regression methods. The results of the study found that the target Financial and Nature of industry had an effect on fraudulent financial statements. Meanwhile, Financial stability, External pressure, and Ineffective monitoring, Change in auditors, Rationalization, and Change of directors, and CEO's picture, have no effect on fraudulent financial statements in mining companies in Indonesia.